An econometric analysis of energy revenue and government expenditure shocks on economic growth in Trinidad and Tobago - Jeetendra Khadan (Inter-American Development Bank (IDB), 2016)
Energy revenues represent roughly 45 percent of Trinidad and Tobago's GDP and are highly volatile since they are correlated with the price of oil and gas. Hence, sharp changes in energy prices, whether temporary or sustained, can have important consequences for economic growth and overall macroeconomic performance. After the 2014 crash in oil prices, a key challenge that emerged for policymakers in hydrocarbon-exporting countries is how to manage fiscal retrenchment in an environment of subdued growth. Using structural vector autoregression, this article examines three questions related to this challenge by focusing on Trinidad and Tobago: (1) what is the asymmetric effect of energy revenue shocks on macroeconomic performance, (2) what is the asymmetric effect of energy revenue shocks on government expenditure (disaggregated by categories), and (3) what is the effect of government expenditure shocks (disaggregated by categories) on economic growth. The results suggest that although positive energy revenue shock increases growth almost immediately, it is not sustained. A negative energy revenue shock is found to have a greater adverse effect on primary expenditure than a positive shock and this largely occurs through a reduction in capital expenditure. Transfers and subsidies, and goods and services are the most sensitive components of current expenditure to positive energy shocks. With respect to the effect of expenditure on growth, transfers and subsidies significantly reduce growth in the short run, whereas other categories of expenditure are found to have a largely positive effect on growth. These findings suggest three important implications for policymakers: the first is to reduce and or reorient public expenditure away from transfers and subsidies and towards more growth-enhancing areas; the second is the need for clear fiscal rules, and to more effectively balance the role of fiscal policy as a growth stimulus while also performing other social functions; and thirdly, these results bring into sharp focus the effectiveness of the rules of the country's stabilization fund to manage windfall energy revenues.
Keywords: E32; E37; Q33; 330; energy revenue shocks; government expenditure; structural vector autoregressive models; Trinidad and Tobago